Nurse handover: patient and staff experiences - Bruton,J; Norton,C; Smyth,N; Ward,H; Day,S (British Journal of Nursing, 2016)
AIM AND OBJECTIVES: to understand the purpose, impact and experience of nurse handover from patient and staff perspectives. BACKGROUND: poor communication is increasingly recognised as a major factor in healthcare errors. Handover is a key risk point. Little consensus exists regarding the practice in nursing but the trend is towards bedside handover. Research on patient and staff experiences of handover is limited. DESIGN: a qualitative and observational study on two acute wards in a large urban hospital in the UK. METHODS: interviews conducted with patients and staff and observation of handovers, ward rounds and patient-staff interactions. RESULTS: diverse forms of nurse handover were found, used in combination: office based (whole nursing team), nurse in charge (NIC) to NIC, and bedside. Patients' and nurses' views concurred on the purpose of bedside handover-transference of information about the patient between two nurses-and about the medical ward round, which was seen as a discussion with the patient. Views diverged regarding the purpose and value of office handover. Bedside handover differed in style, content, and place of delivery, often driven by concerns regarding confidentiality and talking over patients, and there were varied views on the benefits of patient involvement in bedside handover. Nurses worked beyond their shift end to complete handover. Communication problems within the clinical team were identified by staff and patients. CONCLUSIONS: while it is important to agree the purpose of handover and develop appropriate structure, content and style, it need not be a uniform process in all clinical areas. Nurse training to deliver bedside handover and patient information on the purpose of handover and the patient's role would be beneficial.